Global issues politics, economics, and culture - Payne, Richard J. (Pearson, 2013)
Updated in its 4th edition, Global Issues is a current and topical look at the forces driving globalization. From democratization, human rights, and global finance to terrorism, pandemics, and climate change, this texts surveys global problems that transcend boundaries and are challenging the international system. This is the only text of its kind to place complex issues into comprehensive context and thus explain the growing political, economic, and cultural interdependence visible in the headlines and in readers' lives.